2014
DOI: 10.1063/1.4869210
|View full text |Cite
|
Sign up to set email alerts
|

Induced spin-polarization of EuS at room temperature in Ni/EuS multilayers

Abstract: Ni/EuS multilayers with excellent multilayer sequencing are deposited via e-beam evaporation on the native oxide of Si(100) wafers at 4 × 10−9 millibars. The samples have very small surface and interface roughness and show sharp interfaces. Ni layers are nanocrystalline 4–8 nm thick and EuS layers are 2–4 nm thick and are either amorphous or nanocrystalline. Unlike for Co/EuS multilayers, all Eu ions are in divalent (ferromagnetic) state. We show a direct antiferromagnetic coupling between EuS and Ni layers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…EuS thin films with a thickness of 25 nm are largely transparent in the visible region, although the UV-Vis spectra show a broad absorption band between 1.8 and 2.8 eV, caused by the transition from the 4f 7 ground state to the 4f 6 5d configuration in Eu 2+ (Figure 2a). This is in line with EuS being a natural ferromagnetic semiconductor [22], showing an optical band gap of 1.65 eV for thin film EuS [23]. EuS thin films with a thickness of 25 nm deposited at 250 °C on Si (100) wafer show a good crystallinity with preferential growth orientation of the (200) planes parallel to the substrate.…”
Section: Resultssupporting
confidence: 71%
“…EuS thin films with a thickness of 25 nm are largely transparent in the visible region, although the UV-Vis spectra show a broad absorption band between 1.8 and 2.8 eV, caused by the transition from the 4f 7 ground state to the 4f 6 5d configuration in Eu 2+ (Figure 2a). This is in line with EuS being a natural ferromagnetic semiconductor [22], showing an optical band gap of 1.65 eV for thin film EuS [23]. EuS thin films with a thickness of 25 nm deposited at 250 °C on Si (100) wafer show a good crystallinity with preferential growth orientation of the (200) planes parallel to the substrate.…”
Section: Resultssupporting
confidence: 71%
“…During the last years, a tremendous search for novel functional materials put lanthanide-based systems in the focus of research activities aiming at the development of new applications for novel spintronic, energy-storage, light-emitting, and ultrahigh-speed optical devices as well as biomedical applications. There are two general approaches for designing such compounds and systems which consist of either the discovery of new classes of materials or the reexamination and improvement of the properties and the quality of already existing materials. …”
mentioning
confidence: 99%
“…Because of their simple (NaCl) crystal structure and localized spin-only moments on the Eu sites, EuX are often considered as ideal model substances for classical Heisenberg magnets. Despite their discovery in the beginning of the 1960s, , these materials continuously attracted intense research interest, in particular in the development of spintronics applications . In expectation of novel functionalities, the focus moved recently to the investigation of multilayer sequences as well as interfaces with magnetically active topological materials. Although its low Curie temperature ( T C ) of 16.5 K prevents the direct usage of EuS in devices, it was shown that, when thin layers of EuS are combined with Co or Ni, a significant spin polarization in EuS is observable even at room temperature because of the proximity effect. A significant improvement in the quality of EuS films on technologically relevant substrates like InAs(100) and InP(100) was reported recently, giving good hope for further developments of EuS-based heterostructures for magnetic applications. , Despite all of these developments and achievements, a detailed description of the electronic structure of EuS itself is still missing. Although its sister material EuO was recently the focus of angle-resolved photoelectron spectroscopy (ARPES) studies, , there is a lack of information on EuS and, in particular, how its electronic structure is modified when the system undergoes a transition to the ferromagnetic phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations